Germline DNA Retention in Murine and Human Rearranged T Cell Receptor Gene Coding Joints: Alternative Recombination Signal Sequences and V(D)J Recombinase Errors - Mika, Justyna; Kabacik, Sylwia; Badie, Christophe; Polanska, Joanna; Candéias, Serge M. (Frontiers in Immunology, 2019)
The genes coding for the antigenic T cell receptor (TR) subunits are assembled in thymocytes from discrete V, D and J genes by a site-specific recombination process. A tight control of this activity is required to present potentially detrimental recombination events. V, D and J genes are flanked by semi-conserved nucleotide motives called recombination signal sequences (RSSs). V(D)J recombination is initiated by the precise introduction of a DNA double strand break exactly at the border of the genes and their RSSs by the RAG recombinase. RSSs are therefore physically separated from the coding region of the genes before assembly of a rearranged TR gene. During a high throughput profiling of TRB genes in mice, we identified rearranged TRB genes in which part or all of a flanking RSS was retained in V-D or D-J coding joints. In some instances, this retention of germline DNA resulted from the use of an upstream alternative RSS. However, we also identified TRB sequences where retention of germline DNA occurred in the absence of alternative RSS, suggesting that RAG activity was mis-targeted during recombination. Similar events were also identified in human rearranged TRB and TRG genes. The use of alternative RSSs during V(D)J recombination illustrates the complexity of RAG-RSSs interactions during V(D)J recombination. While the frequency of errors resulting from mis-targeted RAG activity is very low, we believe that these RAG errors may be at the origin of oncogenic translocations and are a threat for genetic stability in developing lymphocytes.